Negative plate and battery
By adopting a double-layer coating design on the negative electrode of lithium-ion batteries, the distribution of siliceous carbon particles and graphite particles is regulated, and the expansion and lithium-ion problems of silicon-carbon materials blended with graphite negative electrode are solved, which significantly improves the circulation and rate performance of the battery .
Patent Information
- Application Number
- CN202411576606.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Silicon-carbon material blended graphite negative electrode has problems such as expansion and easy lithium dissipation in lithium-ion batteries, which has affected the battery cycle life and safety, limiting its wide application in the field of lithium batteries.
The design of a double-layer coated negative electrode sheet is used to regulate the spatial position of the silica carbon particles and the particle size of the upper and lower graphite particles to suppress expansion and lithium evolution. Specific measures include mixing graphite particles of different particle sizes in the first coating, adding silicon carbon particles to the second coating, and providing several recesses on the surface of the active material layer.
It significantly improves the circulation performance and rate performance of lithium-ion batteries, extends the cycle life of the battery, reduces the risk of expansion, and improves the energy density and capacity stability of the battery.
Smart Images

Figure CN119447174A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode sheet and a battery. Background Art
[0002] With the increasing requirements for the energy density of lithium batteries, silicon-carbon materials mixed with graphite negative electrodes have attracted attention as a potential alternative material; however, silicon-carbon materials mixed with graphite negative electrodes face two main problems: large expansion and easy lithium precipitation; large expansion, silicon-containing particles will undergo drastic volume expansion and contraction during the process of lithium insertion and extraction, which can easily cause the graphite particles to twist, causing swelling and deformation of lithium-ion batteries, affecting the cycle life and safety of the battery; easy lithium precipitation, silicon-based negative electrode materials are prone to lithium precipitation during the charging process due to slow kinetics, which can easily lead to a decrease in battery capacity; the above problems have severely limited the widespread application of silicon-carbon materials mixed with graphite negative electrodes in the field of lithium batteries. Summary of the invention
[0003] Based on the above problems, the present invention proposes a negative electrode sheet with a double-layer coating, which can suppress the expansion problem and lithium precipitation problem of the silicon-carbon material mixed with the graphite negative electrode by regulating the spatial position of the silicon-carbon particles and the particle size of the upper and lower graphite particles, thereby significantly improving the cycle performance and rate performance of the lithium-ion battery.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A first aspect of the present invention provides a negative electrode sheet, comprising a current collector and an active material layer located on at least one side of the current collector, wherein the active material layer comprises a first coating layer close to the surface of the current collector and a second coating layer away from the surface of the current collector;
[0006] The first coating layer comprises first graphite particles and second graphite particles, the particle size Dv150 of the first graphite particles is 5 μm-12 μm, the particle size Dv250 of the second graphite particles is 10 μm-16 μm, and the particle size Dv250 of the second graphite particles is greater than the particle size Dv150 of the first graphite particles;
[0007] The second coating layer comprises third graphite particles and silicon-carbon particles, the particle size Dv350 of the third graphite particles is 4 μm-11 μm; the particle size Dv450 of the silicon-carbon particles is 5 μm-12 μm;
[0008] The surface of the active material layer is provided with a plurality of recesses.
[0009] A second aspect of the present invention provides a battery, the battery comprising a negative electrode sheet and a separator, the negative electrode sheet being the negative electrode sheet according to the first aspect of the present invention;
[0010] Preferably, the bonding force between the negative electrode sheet and the separator is 0.284N-0.428N.
[0011] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0012] (1) The negative electrode provided by the present invention places silicon-carbon particles on the surface of the coating of the negative electrode, which can make them expand first during charging to inhibit the expansion of the underlying graphite particles, thereby inhibiting the expansion of the entire battery, reducing the stress effect on the battery structure, and improving the cycle life of the battery;
[0013] (2) The negative electrode provided by the present invention can reduce lithium precipitation of silicon-carbon materials during the charging and discharging process by placing small-size fast-charging graphite particles on the surface of the coating of the negative electrode, thereby improving the stability and predictability of battery capacity;
[0014] (3) The negative electrode provided by the present invention helps to improve the energy density of lithium batteries by optimizing the spatial position of silicon-carbon particles and the size of graphite particles in the upper and lower coatings, thereby meeting the demand for high-energy-density batteries in modern electronic products;
[0015] (4) The active material layer on the surface of the negative electrode provided by the present invention is provided with a plurality of recesses, which can further solve the lithium deposition problem of the silicon-doped negative electrode.
[0016] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A schematic structural diagram of a negative electrode sheet according to an embodiment of the present invention.
[0018] Figure 2 This is a partial enlarged view of a negative electrode sheet in an example provided by the present invention.
[0019] Description of reference numerals:
[0020] Current collector-1, first coating layer-2, second coating layer-3, transition layer-4, recess-5. DETAILED DESCRIPTION
[0021] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0022] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0023] A first aspect of the present invention provides a negative electrode sheet, such as Figure 1 The figure shows a schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present invention, comprising a current collector 1 and an active material layer located on at least one side of the current collector 1, wherein the active material layer comprises a first coating layer 2 close to the surface of the current collector 1 and a second coating layer 3 away from the surface of the current collector; wherein the first coating layer 2 is a bottom coating layer closer to the surface of the current collector 1, and the second coating layer 3 is a top coating layer located on the surface of the first coating layer 2 away from the current collector 1, that is, located on the surface of the entire negative electrode sheet.
[0024] In the present invention, the first coating layer comprises first graphite particles and second graphite particles, and the particle size Dv250 of the second graphite particles is greater than the particle size Dv150 of the first graphite particles.
[0025] In the present invention, the particle size Dv150 of the first graphite particles is 5 μm-12 μm. Exemplarily, the particle size Dv150 of the first graphite particles can be 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm. In a preferred embodiment, the particle size Dv150 of the first graphite particles is 7 μm-10 μm.
[0026] In the present invention, the particle size Dv250 of the second graphite particles is 10 μm-16 μm. Exemplarily, the particle size Dv250 of the second graphite particles can be 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm. In a preferred embodiment, the particle size Dv250 of the second graphite particles is 12 μm-15 μm.
[0027] In the present invention, the second coating layer comprises third graphite particles and silicon-carbon particles, the particle size Dv350 of the third graphite particles is 4 μm-11 μm, and exemplary, the particle size Dv350 of the third graphite particles can be 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm. In a preferred embodiment, the particle size Dv50 of the third graphite particles is 7 μm-10 μm.
[0028] In the present invention, the second coating layer comprises third graphite particles and silicon-carbon particles, and the particle size Dv450 of the silicon-carbon particles is 5 μm-12 μm. Exemplarily, the particle size Dv450 of the silicon-carbon particles can be 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm. In a preferred embodiment, the particle size Dv450 of the silicon-carbon particles is 6 μm-9 μm.
[0029] The negative electrode provided by the present invention places silicon-carbon particles on the surface layer of the coating of the negative electrode sheet, which can cause the silicon-carbon particles to expand first during charging to suppress the expansion of the underlying graphite particles, thereby suppressing the expansion of the entire battery, reducing the stress effect on the battery structure, and improving the cycle life of the battery.
[0030] Furthermore, since the particle size of the graphite particles in the active material layer is too small, it may cause more serious side reactions, thereby affecting the cycle life of the battery; if the particle size of the graphite particles is too large, the solid-phase diffusion kinetics during the charge and discharge process is poor, which is easy to affect the rate charge and discharge capacity of the battery; therefore, the present invention uses a mixture of graphite particles of different particle sizes in the first coating layer close to the current collector, that is, the active material of the first coating layer is set to include small-particle first graphite particles and large-particle second graphite particles at the same time, so as to take into account both the cycle life and the rate charge and discharge capacity of the battery. In addition, the small-particle first graphite particles can be dispersed in the gaps between the large-particle second graphite particles, providing a buffer for the cyclic expansion of the small-particle first graphite particles in the late cycle, and also providing a buffer for the expansion of the silicon-carbon particles in the second coating layer, which is further beneficial to alleviate the expansion phenomenon of the overall battery and improve the cycle stability of the battery.
[0031] Furthermore, since the reaction kinetics of silicon-carbon particles are poorer than those of graphite particles, smaller silicon-carbon particles are selected to be mixed with small third graphite particles to form a second coating. This can optimize the fast charging kinetics of the surface of the active material layer to a certain extent, thereby ensuring that the battery meets the technical requirements of fast charging, reducing lithium precipitation of silicon-carbon materials during the charging and discharging process, greatly optimizing the risk of lithium precipitation, and thus improving the stability and predictability of the battery capacity.
[0032] In summary, the negative electrode sheet provided by the present invention avoids the expansion problem of silicon-carbon material mixed with graphite negative electrode by optimizing the spatial position of silicon-carbon particles and the size of graphite particles in the upper and lower coatings, thereby helping to improve the energy density of lithium batteries and meeting the needs of modern electronic products for high-energy density batteries; moreover, it improves the fast charging kinetics of the surface layer of the active material layer, thereby greatly optimizing the risk of lithium precipitation, reducing lithium precipitation of silicon-carbon materials during the charging and discharging process, and thus significantly improving the cycle performance and rate performance of lithium-ion batteries.
[0033] The particle size Dv50 of each of the above particles can be obtained by taking the average value after testing with a particle size tester. The particle size Dv50 is the particle size of particles that account for 50% of the volume distribution. The testing method is: using a Malvern MS3000 particle size tester to test it. The setting test conditions of the particle size tester are: refractive index 2.1, absorptivity 1.0, shading 8-12%, water (or ethanol) is used as the dispersant, and the stirring rate is 2500rpm. According to the above steps, the test is performed 3 times, and the average value of the 3 results is taken to obtain the particle size Dv50 of each particle.
[0034] In addition, according to the negative electrode sheet of the present invention, the surface of the active material layer is provided with a plurality of recesses. Figure 1 As shown, the surface of the active material layer is provided with a plurality of concave portions, which may include holes, grooves, etc. The concave portion structure is generally obtained by processing the surface of the active material layer through laser wire-making technology. Laser wire-making is a technology for making fine grooves on the active material layer on the surface of the negative electrode sheet. It is mainly used in the production of lithium batteries. This technology can effectively improve the performance of the battery, increase the charging and discharging efficiency and cycle life of the battery.
[0035] Therefore, the present invention uses laser wire-punching technology to process the active material layer on the surface of the negative electrode sheet, so that a number of recessed structures are formed on the active material layer, and specific lithium ion transmission channels can be formed in the active material layer of the negative electrode sheet. These channels are conducive to the rapid transmission of lithium ions and increase the migration number of lithium ions, thereby avoiding the accumulation and precipitation of ions, and further improving the lithium precipitation problem of silicon-doped negative electrode sheets; moreover, when a number of recesses are provided on the surface of the active material layer, expansion sites and expansion space can also be provided for the expansion of the active material particles in the first coating or the second coating, thereby further improving the expansion problem of the silicon-carbon material-doped negative electrode sheet and improving the cycle stability of the lithium-ion battery.
[0036] In order to further enhance the performance improvement brought about by the particle size settings of the above-mentioned coatings, according to the negative electrode sheet of the present invention, based on the total mass of the first coating, the mass ratio of the first graphite particles to the second graphite particles is (8-12):(88-92); illustratively, the mass ratio of the first graphite particles to the second graphite particles can be 8:92, 9:91, 10:90, 11:89, 12:88, and the sum of the previous and subsequent values is 100. When the mass ratio of two graphite particles of different sizes exceeds this range, it may lead to violent side reactions inside the battery during a long cycle, resulting in problems such as capacity diving and accelerated expansion. For example, when the mass proportion of the first graphite particles is too high, the degree of side reactions between the active material layer of the negative electrode sheet and the electrolyte will increase, which will cause the reaction to consume more electrolyte; and when the mass proportion of the second graphite particles is too high, the porosity of the first coating will increase, thereby causing the energy density of the battery to decrease; therefore, the present invention can better achieve a balance between the short-term fast charging performance and the long-term cycle life of the battery by adjusting the mass ratio of the first graphite particles to the second graphite particles in the first coating.
[0037] According to the negative electrode sheet of the present invention, the mass ratio of the silicon-carbon particles to the third graphite particles is (22-38): (62-78). Exemplarily, the mass ratio of the silicon-carbon particles to the third graphite particles can be 22:78, 25:75, 30:70, 35:65, 38:62, and the sum of the values before and after is 100. When the mass ratio of silicon-carbon particles to the third graphite particles exceeds this range, for example, when the mass ratio of silicon-carbon particles is too high, due to the increase in the expansion of silicon-carbon particles, the active material layer will further squeeze the diaphragm, causing a micro-short circuit phenomenon in the negative electrode sheet; in addition, it may also cause the binder to fail, the conductive network to be disconnected, and there is a risk of capacity diving; and when the mass ratio of the third graphite particles is too high, it will cause the negative electrode active material to have a large degree of side reaction with the electrolyte, thereby consuming more electrolyte; therefore, the present invention can further achieve improvement and balance of battery fast charging performance, expansion problems and long cycle life by adjusting the mass ratio of silicon-carbon particles to the third graphite particles in the second coating.
[0038] According to the negative electrode sheet of the present invention, the specific surface area S1 of the first graphite particles is 0.1 m 2 / g-5m 2 / g, illustratively, the specific surface area S1 of the first graphite particles can be 0.1m 2 / g, 0.2m 2 / g, 0.21m 2 / g, 0.22m 2 / g, 0.23m 2 / g, 0.24m 2 / g, 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g; In a preferred embodiment, the specific surface area S1 of the first graphite particles is 0.2m 2 / g-0.24m 2 / g.
[0039] According to the negative electrode sheet of the present invention, the specific surface area S2 of the second graphite particles is 0.1 m 2 / g-5m 2 / g, illustratively, the specific surface area S2 of the second graphite particles can be 0.1m 2 / g, 0.13m 2 / g, 0.14m 2 / g, 0.15m 2 / g, 0.16m 2 / g, 0.17m 2 / g, 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 In a preferred embodiment, the specific surface area S2 of the second graphite particles is 0.13 m 2 / g-0.17m 2 / g.
[0040] The first graphite particles and the second graphite particles are the main materials in the active material layer of the negative electrode sheet. If the specific surface area BET is too large, the contact area between the active material layer and the electrolyte will be larger, and the risk of side reactions will be greater, which is not conducive to the long cycle performance of the battery. If the specific surface area BET is too small, the current distributed to the surface of the particles will be larger under the same load current, which means that the particles have to withstand an actual rate higher than the load rate, which is not conducive to fast charging capability. Therefore, the present invention can further improve the cycle performance and fast charging performance of the battery by adjusting the specific surface area of the first graphite particles and the second graphite particles in the first coating.
[0041] According to the negative electrode sheet of the present invention, the specific surface area S3 of the third graphite particles is 0.1 m 2 / g-6m 2 / g, illustratively, the specific surface area S3 of the third graphite particles may be 0.1m 2 / g, 0.2m 2 / g, 0.21m 2 / g, 0.22m 2 / g, 0.23m 2 / g, 0.24m 2 / g, 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 In a preferred embodiment, the specific surface area S3 of the third graphite particles is 0.2 m 2 / g-0.24m 2 / g.
[0042] According to the negative electrode sheet of the present invention, the specific surface area S4 of the silicon-carbon particles is 0.2 m 2 / g-5m 2 / g, for example, the specific surface area S4 of the silicon-carbon particles can be 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2In a preferred embodiment, the specific surface area S4 of the silicon-carbon particles is 0.5 m 2 / g-1m 2 / g.
[0043] When the specific surface area of silicon-carbon particles is too large, the volume expansion will be aggravated. When the specific surface area of silicon-carbon particles is too small, the insertion and deinsertion channels of lithium ions will be reduced, limiting the battery reaction kinetics and reducing the charge and discharge rates. Therefore, by regulating the specific surface area S4 of silicon-carbon particles, the expansion problem of silicon-doped graphite negative electrode can be further suppressed and the battery rate performance can be improved.
[0044] The test method for the specific surface area of each of the above particles is the gas adsorption BET method. Specifically, the particle sample to be tested is placed in a sample tube, nitrogen is introduced at low temperature (usually using liquid nitrogen), and the adsorption partial pressure is directly measured by controlling the equilibrium pressure in the sample tube, thereby obtaining the adsorption amount. Then, the monolayer adsorption amount is calculated according to the BET equation, thereby obtaining the specific surface area of the particle (unit: m 2 / g).
[0045] According to the negative electrode sheet of the present invention, the OI value of the first coating layer is 12-18, and illustratively, the OI value of the first coating layer may be 12, 13, 14, 15, 16, 17, 18; the OI value of the second coating layer is 9-13, and illustratively, the OI value of the second coating layer may be 9, 10, 11, 12, 13. The OI value (Orientation Index) is a parameter for measuring the crystal orientation of graphite particles in the coating layer. Due to the introduction of silicon-carbon particles and the expansion of the third graphite particles during the formation and sorting process, the OI value of the second coating layer is relatively low and generally lower than the OI value of the first coating layer. However, the OI value of the second coating layer should not be too low, so it is necessary to control its OI value within a suitable range to further improve the kinetic performance of the negative electrode.
[0046] Furthermore, the OI value of the first coating is larger than the OI value of the second coating, that is, the OI value of the first coating is greater than the OI value of the second coating, because the first coating does not contain silicon-carbon particles. This setting can also prevent the silicon-carbon particles from expanding too much, causing the negative electrode active material layer and the current collector to delaminate, further improving the safety and long-term cycle stability of the negative electrode sheet.
[0047] It should be noted that the OI value of the first coating or the second coating is obtained based on the X-ray diffraction (XRD) technology. Specifically, the active material of the first coating or the second coating to be tested is prepared into a thin film or powder sample and placed on the sample stage of the XRD instrument; then the sample is scanned using the XRD instrument to obtain its X-ray diffraction spectrum. According to the intensity ratio of specific diffraction peaks, as well as the calculation formula and analysis method, the OI value corresponding to the first coating or the second coating can be obtained by calculation.
[0048] According to the negative electrode sheet of the present invention, the thickness of the first coating layer is 15 μm-27 μm. For example, the thickness of the first coating layer can be 15 μm, 16 μm, 17 μm, 17.5 μm, 18 μm, 18.5 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm. In a preferred embodiment, the thickness of the first coating layer is 17 μm-25 μm.
[0049] According to the negative electrode sheet of the present invention, the thickness of the second coating layer is 8 μm-20 μm. For example, the thickness of the second coating layer can be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 17.5 μm, 18 μm, 18.5 μm, 19 μm, 20 μm. In a preferred embodiment, the thickness of the second coating layer before rolling is 15 μm-19 μm.
[0050] The present invention adopts a double-layer coating design on the negative electrode sheet, controls the particle size of the upper and lower graphite particles and silicon-carbon particles respectively, and adjusts the thickness of the first coating layer and the second coating layer respectively, which can further improve the volume expansion problem of the negative electrode sheet. In the present invention, a coating machine with a double nozzle can be used to simultaneously apply the slurry of the first coating layer and the slurry of the second coating layer to the surface of the current collector, and the thickness of the coating layer can be adjusted by controlling the coating amount of the coating machine. In addition, it should be noted that the thickness of the first coating layer and the second coating layer is the thickness of the coating layer in the formed negative electrode sheet after being coated by the coating machine and compacted by the roller pressing process, which can be obtained by observing the cross-sectional SEM image of the negative electrode sheet.
[0051] According to the negative electrode sheet of the present invention, the second coating 3 and the first coating 2 in the negative electrode sheet are embedded with each other to form a transition layer 4, and the transition layer 4 is located between the first coating 2 and the second coating 3, and the thickness of the transition layer 4 is d. Figure 2As shown, it is a partial enlarged view of the negative electrode sheet in an example of the present invention, a is the thickness of the second coating 3, b is the thickness of the first coating 2, d is the thickness of the transition layer 4, and the value range of d is 3μm≤d≤4.5μm. Exemplarily, the transition layer d can be 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm. After the negative electrode sheet is rolled, the silicon-carbon particles in the second coating layer will be partially embedded in the graphite particles in the first coating layer, and the graphite particles in the first coating layer will also be partially embedded in the silicon-carbon particles in the second coating layer. Therefore, a transition layer will be formed between the first coating layer and the second coating layer due to the mutual embedding of the two coating layers. The embedding depth of the second coating layer and the first coating layer is the thickness d of the formed transition layer, and the thickness d of the transition layer depends on the rolling strength when the negative electrode sheet is rolled. The mutual embedding of some particles will not affect the effects of the first coating layer and the second coating layer, but it is generally necessary to control the thickness d of the transition layer within an appropriate range to avoid the silicon-carbon particles in the second coating layer from being embedded too deeply in the first coating layer, otherwise it will cause the thickness of the transition layer to be too thick, thereby aggravating the cyclic expansion of the first graphite particles and the second graphite particles in the first coating layer, affecting the long-term cycle life of the battery. In addition, it should be noted that since the morphology of silicon-carbon particles in the transition layer is different from that of the three graphite particles, its position in the transition layer is easier to observe. Therefore, the observation and calculation method of the thickness d of the transition layer can generally be obtained by measuring the average distance of the silicon-carbon particles from the surface of the active material layer after the negative electrode sheet is rolled and the thickness of the second coating, and then calculating the difference between the two; wherein, the average distance of the silicon-carbon particles from the surface of the active material layer after the negative electrode sheet is rolled refers to the statistical distance of different silicon-carbon particles from the surface of the active material layer after the negative electrode sheet is rolled, and the average value of all statistical distances is calculated, which is the average distance of the above silicon-carbon particles from the surface of the active material layer. When actually measuring the distance of different silicon-carbon particles, 3-5 different silicon-carbon particles can be randomly selected. It can be understood that the average distance of the silicon-carbon particles from the surface of the active material layer is calculated because after the negative electrode sheet is rolled, different independent silicon-carbon particles are embedded in the first coating at different positions, so the distance relative to the surface of the active material layer will be different. By calculating the average distance, the accuracy of measuring the embedding position of silicon-carbon particles and the thickness of the transition layer can be improved.
[0052] According to the negative electrode sheet of the present invention, the depth of the recess 5 is h, satisfying the relationship -3.5≤had≤1 (for example, -3.5, -3, -2.5, -2, -1.5, -1, -0.5, 0, 0.5, 1), wherein a is the thickness of the second coating layer, 8μm≤a≤20μm, for example, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm, 37μm, 38μm, 39μm, 40μm, 41μm, 42μm, 43μm, 44μm, 45μm, 46μm, 47μm, 48μm, 49μm, 50μm, 51μm, 52μm, 53μm, 54μm, 55μm, 56μm, 57μm, 58μm, 59μm, 60μm, 61μm, 62μm, 63μm, 64μm 8μm, 19μm, 20μm; d is the thickness of the transition layer formed by the second coating layer and the first coating layer in the negative electrode sheet being embedded with each other, 3μm≤d≤4.5μm, for example, 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm; Figure 2 shown.
[0053] The punching depth of the concave portion is mainly determined by the thickness design ratio of the double-layer coating and the thickness d of the transition layer formed by the mutual embedding of the second coating and the first coating. When h satisfies the relationship -3.5≤had≤1, it can ensure that the punching depth of the concave portion just penetrates the second coating containing silicon-carbon particles (-3.5≤had). The thickness d of the transition layer can also be taken into consideration to avoid the transition layer where the first coating and the second coating are mutually embedded being missed, and to avoid the transition layer being penetrated too deeply (had≤1, 1 is a margin). This is because if the depth of the wire punching in the concave part is too shallow (the second coating containing silicon-carbon particles is not penetrated), the improvement of ion transport kinetics brought by wire punching will not be obvious, and it is still difficult for lithium ions to be transported to the first coating. Therefore, the main reaction area is concentrated in the second coating on the surface, and the material utilization is uneven, which will cause adverse effects such as lithium precipitation. If the depth of the wire punching in the concave part is too deep (the transition layer is penetrated, but the depth of the first coating is too deep), it will cause excessive loss of negative electrode active materials, and the NP ratio (the ratio of the negative electrode capacity to the positive electrode capacity of the battery) may be affected. Although the ion transport kinetics are improved, the reaction sites are reduced, which may also cause adverse effects such as lithium precipitation. Therefore, it is necessary to control the depth h of the concave part so that it is controlled between the depth of just penetrating the second coating and the depth of just penetrating the transition layer, so as to further avoid the lithium precipitation problem caused by the negative electrode sheet including silicon-carbon particles.
[0054] In addition, in a specific embodiment, Figure 2 As shown, the thickness b of the first coating is 15μm-27μm; for example, the thickness b of the first coating can be 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, or 27μm.
[0055] According to the negative electrode sheet of the present invention, Figure 2 As shown, the depth of the recess 5 can be 12μm-25.5μm; for example, the depth of the recess can be 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 17.5μm, 18μm, 18.5μm, 19μm, 19.5μm, 20μm, 20.5μm, 21μm, 21.5μm, 22μm, 22.5μm, 23μm, 23.5μm, 24μm, 24.5μm, 25.5μm. The depth of the recess 5 refers to the vertical distance from the deepest part of the recess to the horizontal plane where the recess opening is located, as shown in FIG. Figure 2 As shown, the depth can reflect the loss of active materials, so it should not be too deep. However, too shallow may lead to little improvement in the lithium deposition problem. Therefore, it is necessary to avoid the above problem by controlling the depth range of the recess within the above range.
[0056] In a specific embodiment, the ratio of the width to the depth of the recess is 4-6; illustratively, the ratio of the width to the depth of the recess may be 4, 4.1, 4.2, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5. When the ratio of the width to the depth of the recess is less than 4, it means that the width of the recess is too narrow and the depth is too deep, which will lead to a large loss of active materials, and the acceleration effect of the narrow channel on lithium ion transmission is not obvious, and the improvement in kinetics is relatively small, which is not conducive to the overall performance; when the ratio of the width to the depth of the recess is greater than 6, it means that the width of the recess is too wide and the depth is too shallow, which will also lead to an unobvious improvement in kinetics. In addition, it should be noted that the width of the recess refers to the vertical distance between the two points farthest apart from each other in the cross-sectional view of the recess perpendicular to the surface of the negative electrode sheet. For example, when the width of the upper and lower layers of the cross-sectional view of the recess are not equal, that is, it is trapezoidal, the width of the recess refers to the width of the wider upper layer, such as Figure 2 shown.
[0057] In the present invention, the cross-sectional shape of the concave portion may be any shape such as a rectangle, a trapezoid, a triangle, etc., and is not limited in the negative electrode sheet of the present invention.
[0058] The cross-sectional morphology of the concave portion can be adjusted by setting the wire bonding parameters, and there is no special restriction in the negative electrode sheet of the present invention. However, it can be found through testing that when the cross-sectional line morphology of the concave portion is trapezoidal and the upper and lower width ratio is 2-3, compared with the concave portion with a rectangular cross-sectional line morphology, the loss of active materials can be relatively reduced, and at the same time, there will be no significant impact on the dynamics; and compared with the concave portion with a triangular cross-sectional line morphology, the dynamics can be greatly improved when the loss of active materials is slightly higher; therefore, taking into account the trapezoidal cross-sectional line morphology, the effects of active material loss and kinetic performance optimization can be balanced.
[0059] Therefore, in a preferred embodiment, the cross section of the recess is trapezoidal, and the width ratio of the upper layer to the lower layer of the trapezoid is 2-3. Figure 2 As shown; illustratively, the width ratio of the upper layer to the lower layer in the concave portion may be 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3. When the cross section of the concave portion is trapezoidal, since the hole is punched from the surface of the negative electrode sheet to the depth of the active material layer, the width of the upper layer of the trapezoidal concave portion formed by the concave portion will be wider than the width of the lower layer. Therefore, there is a width ratio of the upper layer width to the lower layer width. Specifically, the width ratio of the upper layer to the lower layer can be calculated by measuring the lengths of the upper and lower sides of the trapezoidal cross section respectively.
[0060] In a specific embodiment, the spacing between adjacent recesses is 0.5mm-1.5mm. For example, the spacing between adjacent recesses is 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, and 1.5mm. If the spacing between adjacent recesses is small, it is easy to cause a large loss of active materials. If the spacing between adjacent recesses is large, the radiation area is too small and the improvement effect on dynamics is not significant. In addition, it should be noted that the line spacing refers to the distance between parallel recesses formed by laser wire-punching technology. When measuring this distance, it is necessary to select the same site in the two recesses.
[0061] According to the negative electrode sheet of the present invention, the concave portion is formed by laser wire-punching; the weight loss rate of the negative electrode sheet after laser wire-punching is 1.1%-2%. Exemplarily, the weight loss rate of the negative electrode sheet after laser wire-punching can be 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%. A weight loss rate higher than 2% will reduce the battery NP ratio and affect the cycle performance. The weight loss rate is higher than 1.5%, mainly considering that the dynamics of the surface layer are relatively poor, and wire-punching is needed to improve it. If the weight loss rate is reduced, it will affect high-rate charging and discharging. In a preferred embodiment, the weight loss rate of the negative electrode sheet after laser wire-punching is 1.5%-1.8%.
[0062] According to the negative electrode sheet of the present invention, the negative electrode potential of the negative electrode sheet is 30mv-82mv. Exemplarily, the negative electrode potential of the negative electrode sheet can be 30mv, 31mv, 32mv, 33mv, 34mv, 35mv, 36mv, 37mv, 38mv, 39mv, 40mv, 45mv, 50mv, 55mv, 60mv, 65mv, 70mv, 75mv, 80mv, 82mv. The negative electrode potential of the negative electrode sheet can be increased by 100-123mv relative to the conventional design. The conventionally designed negative electrode sheet generally has a minimum negative electrode potential of -60 to -50mV under high-rate charging conditions, which has a greater risk of lithium plating, resulting in a rapid decline in battery performance. Compared with conventional designs, the designed negative electrode sheet can greatly improve the negative electrode potential under high-rate charging conditions, reduce the risk of lithium plating of the negative electrode sheet, and thus improve the capacity stability and cycle performance of lithium-ion batteries.
[0063] According to the negative electrode sheet of the present invention, the surface resistance of the negative electrode sheet is 200mΩ-290mΩ. Exemplarily, the surface resistance of the negative electrode sheet can be 200mΩ, 210mΩ, 220mΩ, 230mΩ, 240mΩ, 250mΩ, 260mΩ, 270mΩ, 280mΩ, 290mΩ. Furthermore, the low surface resistance of the negative electrode sheet can reduce the ohmic impedance of the entire electrode sheet, reduce the polarization of the negative electrode, and improve the cycle performance of the lithium-ion battery.
[0064] A second aspect of the present invention provides a battery, the battery comprising a negative electrode sheet and a separator, the negative electrode sheet being the negative electrode sheet according to the first aspect of the present invention;
[0065] The bonding force between the negative electrode sheet and the separator is 0.1N-2N. Exemplarily, the bonding force between the negative electrode sheet and the separator may be 0.1N, 0.2N, 0.21N, 0.22N, 0.23N, 0.24N, 0.25N, 0.26N, 0.27N, 0.28N, 0.29N, 0.3N, 0.31N, 0.32N, 0.33N, 0.34N, 0.35N, 0.36N, 0.37N, 0.38N, 0.39N, 0.4N, 0.41N, 0.42N, 0.428N, 0.429N, 0.43N, 0.5N, 1N, 1.5N, 2N. Since the second coating on the surface of the present invention is a silicon-containing coating, more silicon-carbon particles will contact the diaphragm, and the hydroxyl groups on the surface of the silicon-carbon particles will interact with the diaphragm, so that its adhesion is 2.3 times higher than that of the graphite coating, thereby avoiding the increase in battery impedance and the interface problems caused by the increase in the transmission path of lithium ions due to the poor adhesion between the diaphragm and the negative electrode. In a preferred embodiment, the adhesion between the negative electrode sheet and the diaphragm is 0.2N-0.43N.
[0066] The battery of the present invention also includes a positive electrode sheet. The battery of the present invention can be prepared by conventional methods in the art. Specifically, the negative electrode sheet, the separator and the positive electrode sheet can be stacked in sequence, and then a battery cell can be obtained by a stacking or winding process, and then the above battery can be obtained by baking, liquid injection, formation, packaging and other processes. All materials in the positive electrode sheet, the negative electrode sheet and the separator in the present invention can be prepared according to methods known in the art or obtained through commercial channels.
[0067] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0068] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0069] Example 1
[0070] Preparation of batteries
[0071] 1) Preparation of negative electrode sheet: The first graphite particles and the second graphite particles as well as the silicon-carbon particles and the third graphite particles are mixed into slurry in a certain proportion, the slurry of the first graphite particles and the second graphite particles is placed on the bottom nozzle of the coater, and the slurry of the silicon-carbon particles and the third graphite particles is placed on the top nozzle of the coater, and coated on a 5 μm copper foil at the same time to form a first coating and a second coating, which is then dried, rolled and cut into small pieces of 73 mm*1458 mm.
[0072] Among them, the thickness of the transition layer formed by the mutual embedding of the second coating and the first coating is d=3.5μm, the thickness of the first coating is b is 25μm, and the thickness of the second coating is a is 11μm. Then laser marking is performed, and the marking power is set to 50%. The cross-sectional morphology of the concave portion is trapezoidal (the width ratio of the upper layer to the lower layer is 2.5, the upper layer is 70μm wide, and the lower layer is 28μm wide), the width of the concave portion / the depth of the concave portion h=5 (70μm / 14μm), and the concave spacing = 1mm.
[0073] 2) Preparation of positive electrode:
[0074] LiCoO2: conductive carbon black: PVDF were mixed in a mass ratio of 9.8:0.1:0.1, and then stirred in a planetary mixer for 12 hours; the positive electrode paste was evenly coated on an aluminum foil with a diameter of 8um, placed in an oven at 60°C and dried for 24 hours, and then the positive electrode was cut into a size of 71mm*1456mm to obtain a positive electrode sheet.
[0075] 3) Preparation of electrolyte:
[0076] 1M LiPF6 was dissolved in EC / DMC (1 / 1 mass ratio) to obtain an electrolyte, and 15% by mass of FEC was added.
[0077] 4) Preparation of lithium-ion batteries
[0078] After the positive and negative electrode sheets and separators were wound into an electrode assembly, the electrode assembly was stacked and pressed for 100 seconds at about 90°C and 250kgf using a hot press. Subsequently, the electrode assembly was housed in a case, the electrolyte was injected therein, and then vacuum-sealed.
[0079] Example 2 Group:
[0080] Example 2 was carried out in accordance with Example 1, with the only difference being that the particle size of the particles in the first coating or the second coating was changed, as shown in Tables 1-3 for details.
[0081] Embodiment 3 group:
[0082] Example 3 was carried out with reference to Example 1, except that the mass ratio of the first graphite particles to the second graphite particles in the first coating slurry was changed, specifically:
[0083] Example 3-1, the mass ratio of the first graphite particles to the second graphite particles in the first coating slurry is changed to 8:92;
[0084] In Example 3-2, the mass ratio of the first graphite particles to the second graphite particles in the first coating slurry is changed to 12:88;
[0085] Example 3-3, the mass ratio of the first graphite particles to the second graphite particles in the first coating slurry is changed to 5:95;
[0086] In Example 3-4, the mass ratio of the first graphite particles to the second graphite particles in the first coating slurry is changed to 20:80.
[0087] Embodiment 4 group:
[0088] Example 4 was carried out with reference to Example 1, except that the mass ratio of the silicon-carbon particles to the third graphite particles in the second coating slurry was changed, specifically:
[0089] In Example 4-1, the mass ratio of silicon carbon particles to third graphite particles in the second coating slurry was changed to 22:78;
[0090] In Example 4-2, the mass ratio of silicon carbon particles to third graphite particles in the second coating slurry was changed to 38:62;
[0091] In Example 4-3, the mass ratio of silicon carbon particles to third graphite particles in the second coating slurry was changed to 10:90;
[0092] In Example 4-4, the mass ratio of the silicon-carbon particles to the third graphite particles in the second coating slurry is changed to 50:50.
[0093] Embodiment 5 group:
[0094] Example 5 was carried out in accordance with Example 1, with the only difference being that the parameter setting of the laser wire-making process was changed so that the depth h of the recess was changed, as shown in Table 1-3 for details.
[0095] Embodiment 6:
[0096] Example 6 is carried out with reference to Example 1, the only difference being that the parameter setting of the laser wire-making process is changed so that the cross-sectional shape of the recessed portion is changed, see Table 1-3 for details.
[0097] Embodiment 7 group:
[0098] Example 7 was carried out with reference to Example 1, with the only difference being that the thickness of the first coating layer and the second coating layer were changed, as shown in Table 1-3 for details.
[0099] Comparative Example 1:
[0100] Comparative Example 1 was carried out with reference to Example 1, except that the particle size of the particles in the first coating or the second coating was changed, as shown in Tables 1-3.
[0101] Comparative Example 2:
[0102] Comparative Example 2 was carried out with reference to Example 1, with the only difference being that the slurry in the bottom nozzle was changed to silicon-carbon particles and second graphite particles, as shown in Tables 1-3 for details.
[0103] Comparative Example 3:
[0104] Comparative Example 3 was carried out with reference to Example 1, except that no wire bonding process was performed and no concave portion was provided on the surface of the active material layer. For details, see Table 1-3.
[0105] Table 1
[0106]
[0107]
[0108] Table 2
[0109]
[0110]
[0111] Table 3
[0112]
[0113]
[0114] In Table 3, since the first coating layer and the second coating layer of the active material layer in Comparative Example 2 use the same component, there is no transition layer between the two coating layers, so the thickness d of the transition layer is represented by “\” in the table.
[0115] Negative electrode test example
[0116] The negative electrode sheets prepared in the above examples and comparative examples were subjected to the following tests, and the test results are recorded in Table 4.
[0117] 1) Weight loss rate of negative electrode sheet: The negative electrode sheets prepared in the above embodiments and comparative examples were cut into small pieces and weighed, and weighed again after laser wire bonding. The weight loss rate of the negative electrode sheet (%) = 1-weight after wire bonding / weight before wire bonding × 100%.
[0118] 2) Negative electrode potential of the negative electrode sheet: The negative electrode sheets prepared in the above embodiments and comparative examples are placed in a button cell with a conventional lithium sheet, and then charged and discharged. The displayed voltage is the potential (mv) of the negative electrode sheet.
[0119] 3) Adhesion test between negative electrode sheet and separator: The lithium-ion batteries prepared in the above embodiments and comparative examples were fully charged to 4.5V, the batteries were disassembled, and the positions where the separator / negative electrode had better adhesion were cut into small strips with a width of 15mm and a width of 5cm. The strips were placed in a peeling force tester for testing to obtain the adhesion (N) between the negative electrode sheet and the separator.
[0120] 4) Negative electrode sheet surface resistance test: The half-charged fresh lithium-ion batteries prepared in the above embodiments and comparative examples were disassembled, the negative electrode sheets were taken out, and the surface resistance (mΩ) was tested using a surface resistance meter with a pressure set to 0.2N.
[0121] Lithium-ion battery test example
[0122] The lithium ion batteries prepared in the above examples and comparative examples were subjected to the following tests, and the test results are recorded in Table 4.
[0123] 4) Rate test: The lithium ion batteries prepared in the above embodiments and comparative examples were kept at a constant temperature of 25°C for 10 min, and the rate performance of the lithium ion batteries was tested by 0.1C and 1C discharge in the voltage range of 4.5-3.0V. The amount of electricity that can be discharged at a discharge rate of 1C (based on the amount of electricity discharged at 0.1C) was tested, and the rate performance (%) = the amount of electricity that can be discharged at a discharge rate of 1C / the amount of electricity discharged at 0.1C × 100%.
[0124] 5) Cycle test and lithium precipitation test: The lithium ion batteries prepared in the above embodiments and comparative examples were placed at an ambient temperature of 25°C for 10 min, then charged at 3.5C to 4.35V (constant voltage 1.8C cut-off), charged at 1.8C to 4.4V (constant voltage 1.5C cut-off), charged at 1.5C to 4.53V (constant voltage 1.2C cut-off), charged at 1.2C to 4.58V (constant voltage 0.24C cut-off), discharged at 1C to 3.5V, and discharged at 0.7C to 3V. The above cycle was repeated for 10 min. During the capacity test, the 800-cycle capacity retention rate = 800th-cycle discharge capacity / first-cycle discharge capacity is obtained; then, after the above lithium-ion battery has cycled for 800 cycles, it is charged to 50% SOC at a rate of 1.1C, charged to 4.5V at 0.5C, and charged at a constant voltage cutoff of 0.05C. After standing for 10 minutes, it is removed from the stage for full-charge dissection to observe the status of the outermost and inner negative electrode sheets to determine whether lithium deposition occurs and the severity of lithium deposition, which can be divided into four levels: no lithium deposition, slight lithium deposition, lithium deposition, and severe lithium deposition.
[0125] 6) Full-to-full expansion rate test: The lithium-ion batteries prepared in the above embodiments and comparative examples were fully charged, and their PPG thickness was tested under a force of 600 g. After 800 T of cycles, the thickness was measured again. Full-to-full expansion rate = 1-first full-charge thickness / full-charge thickness after cycles
[0126] 7) Charge transfer impedance: After the lithium ion batteries prepared in the above embodiments and comparative examples were allowed to stand for 10 minutes, they were charged to 4.35V at 3.5C (constant voltage 1.8C cutoff), charged to 4.4V at 1.8C (constant voltage 1.5C cutoff), charged to 4.53V at 1.5C (constant voltage 1.2C cutoff), charged to 4.58V at 1.2C (constant voltage 0.24C cutoff), discharged to 3.5V at 1C, and discharged to 3V at 0.7C.
[0127] Table 4
[0128]
[0129]
[0130] It can be analyzed from Table 4 that the present invention can suppress the expansion problem and lithium precipitation problem of the silicon-carbon material mixed with the graphite negative electrode by adopting a double-layer coated negative electrode sheet and regulating the spatial position of the silicon-carbon particles and the particle size of the upper and lower graphite particles, so that the full-to-full expansion rate of the lithium-ion battery in the embodiment is significantly reduced compared with the comparative example, and the rate performance and cycle capacity retention rate can also be maintained at a high level, thereby being able to simultaneously improve the cycle performance and rate performance of the lithium-ion battery, and the expansion problem is effectively improved.
[0131] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A negative electrode sheet, characterized in that: It includes a current collector and an active material layer located on at least one side of the current collector, wherein the active material layer includes a first coating layer close to the surface of the current collector and a second coating layer away from the surface of the current collector; The first coating layer comprises first graphite particles and second graphite particles, the particle size Dv150 of the first graphite particles is 5 μm-12 μm, the particle size Dv250 of the second graphite particles is 10 μm-16 μm, and the particle size Dv250 of the second graphite particles is greater than the particle size Dv150 of the first graphite particles; The second coating layer comprises third graphite particles and silicon-carbon particles, the particle size Dv350 of the third graphite particles is 4 μm-11 μm; the particle size Dv450 of the silicon-carbon particles is 5 μm-12 μm; The surface of the active material layer is provided with a plurality of recesses.
2. The negative electrode sheet according to claim 1, characterized in that: Based on the total mass of the first coating layer, the mass ratio of the first graphite particles to the second graphite particles is (8-12):(88-92); And / or, based on the total mass of the second coating layer, the mass ratio of the silicon-carbon particles to the third graphite particles is (22-38):(62-78).
3. The negative electrode sheet according to claim 1, characterized in that: The specific surface area S1 of the first graphite particles is 0.1 m 2 / g-5m 2 / g, the specific surface area S2 of the second graphite particles is 0.1m 2 / g-5m 2 / g; And / or, the specific surface area S3 of the third graphite particles is 0.1 m 2 / g-6m 2 / g, the specific surface area S4 of the silicon-carbon particles is 0.2m 2 / g-5m 2 / g.
4. The negative electrode sheet according to claim 1, characterized in that: The OI value of the first coating is 12-18, and the OI value of the second coating is 9-13; The OI value of the first coating is greater than the OI value of the second coating.
5. The negative electrode sheet according to claim 1, characterized in that: The thickness of the first coating layer is 15 μm-27 μm, and the thickness of the second coating layer is 8 μm-20 μm.
6. The negative electrode sheet according to claim 1, characterized in that: The second coating layer and the first coating layer in the negative electrode sheet are embedded in each other to form a transition layer, and the transition layer is located between the first coating layer and the second coating layer. The thickness of the transition layer is d, 3μm≤d≤4.5μm.
7. The negative electrode sheet according to claim 1, characterized in that: The depth of the recess is h, satisfying the relationship -3.5≤had≤1, wherein a is the thickness of the second coating, 8μm≤a≤20μm; d is the thickness of the transition layer formed by the second coating and the first coating in the negative electrode sheet being embedded in each other, 3μm≤d≤4.5μm.
8. The negative electrode sheet according to claim 1, characterized in that: The depth of the concave portion is 12 μm-25.5 μm; Preferably, the ratio of the width to the depth of the recess is 4-6; Preferably, the cross section of the recess is trapezoidal, and the width ratio of the upper layer to the lower layer of the trapezoid is 2-3; Preferably, the spacing between adjacent recesses is 0.5 mm-1.5 mm.
9. The negative electrode sheet according to claim 1, characterized in that: The negative electrode potential of the negative electrode sheet is 30mv-82mv; And / or, the surface resistance of the negative electrode sheet is 200mΩ-290mΩ; preferably 220mΩ-250mΩ.
10. A battery, characterized in that: The battery comprises a negative electrode sheet and a separator, wherein the negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 9; Preferably, the adhesion between the negative electrode sheet and the separator is 0.1N-2N; preferably 0.2N-0.43N.
Citation Information
Patent Citations
Negative pole piece of lithium ion battery, and lithium ion battery using the negative pole piece
CN109585781A
Negative plate and battery
CN113594408A
Secondary battery and electric device
WO2024168477A1
Negative electrode plate, method for preparing same, battery cell, battery, and electric apparatus
WO2024183037A1
Cited By
Negative plate, lithium ion battery and electric device
CN120565564A
Negative electrode sheet and preparation method therefor, battery and electric device
WO2026065892A1